A new name for Ehretia ovalifolia Wight (Ehretiaceae: Boraginales). Issue 2 (2nd July 2016) - Kottaimuthu, R.
Abstract : Ehretia matthewii Kottaim. is proposed here as a replacement name for Ehretia ovalifolia Wight as it is a later homonym of Ehretia ovalifolia Hassk.